INJURIES IN KARATE: STRUCTURE, CAUSES, AND PREVENTION AT DIFFERENT STAGES OF SPORTS TRAINING (Modern American Journal of Medical and Health Sciences, 2025)
This article presents a review of current scientific data on injuries in karate. It examines the structure and mechanisms of sports injuries depending on the discipline (kumite and kata), the conditions of occurrence (competition and training), and the age and skill level of athletes. Based on an analysis of prospective studies, systematic reviews, and international consensus documents, it is shown that injuries in karate are predominantly mild to moderate in nature, but are distinguished by a specific profile with a predominance of contact injuries to the head, face, and upper extremities in kumite and non-contact overuse injuries to the musculoskeletal system in kata and training activities. Particular attention is paid to the causes and risk factors of injuries, and the role of World Health Organization (WHO) regulatory requirements. Karate Federation (WKF) and the importance of a stage-differentiated approach to prevention.